Zagrożenie drzewostanów ze strony huby korzeni w zależności od temperatury gleby i opadów - Mykhayliv, Oksana; Sierota, Zbigniew (Leśne Prace Badawcze, 2010)
The statistical analysis of the relationship between the area where the root rot (Heterobasidion annosum) occurred and soil temperature and precipitation was performed for averaged values from all over Poland and additionally, from three regions differing in terms of climate (the Regional Directorates of State Forests in Białystok, Kraków and Poznań). The data used for comparison comprises occurrence of the root rot in years 1975-2007, divided into the age category up to 20 years and over 20 years. The relationship between the area where the root rot occurs in an n-year and the analysed weather components in years n-l (where l = 0, 1, 2, 3) was investigated with the use of multiple regression analysis following the SAS Enterprise Guide 4 statistical package (2007). In most cases the pattern of soil temperature changes in September, October and in December and precipitation level in June had decisive effects on disease development. The relationship between the root rot and soil temperature and humidity was of regional character and resulted from the tree stand age category under analysis. The obtained values of determination coefficient indicate that the impact of the analysed climatic factors on root rot development was stronger in tree stands over 20 years of age. The strongest correlation relationship was found between the root rot area in tree stands and the analysed weather components in the previous year.